The Role of the Fire King Institution (Yang Pơtao Apui) of Gia Rai Minority in Gia Lai Province in the New Context - Van Thang, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 41 No 2, 2025)
Yang Pơtao Apui (the Fire King) is a unique traditional institution in the social life of the Gia Rai people in particular and the Central Highlands (Tây Nguyên) in general. Throughout history, the Fire Kings have preserved their distinctive cultural identity despite many changes in social life. These cultural values continue to play a meaningful role in the contemporary life of the Gia Rai community. This article focuses on clarifying key perspectives and assessing the role of the Fire King in terms of its origin, development, and functions in community management, spiritual communication, and daily life. Based on fieldwork and collected data, the paper aims to analyze and highlight the current role of the Fire King institution, thereby proposing several solutions to preserve and promote its cultural value in alignment with the Party’s viewpoints and the Government’s policies.